AutoSherlock: a program for effective crystallization data analysis - Nagel, Raymond M. (International Union of Crystallography, 2008)
A program, AutoSherlock, has been developed to present crystallization screening results in terms of chemical space. This facilitates identification of lead conditions, rational interpretation of results and directions for the optimization of crystallization conditions.